Não contem com o fim dos leitores: narrativas e mediação de leitura no canal da booktuber Pam Gonçalves - Costa, Andressa Souza (2020)
To read, signify, co-create, narrate: this sequence routines the practice of booktubers, a group formed mainly by young people who like to read and share impressions about readings in videos posted on YouTube. In a convergence culture (JENKINS, 2009), they take on a new reader profile by bringing together, simultaneously, the conditions of producer and consumer, i.e., prosumer (TOFFLER, 1980; AMARAL, 2012), producing new narratives about their readings and maintaining a conduct marked by engagement. In this research, we seek to understand how literary experiences narrated in YouTube videos act to mediate readings in an online environment, particularly with young people. To do so, we chose to analyze the Pam Gonçalves booktuber channel, one of the oldest, most active and popular producers in the community, whose content dialogues especially with young people. Initially, we discussed the profile of the producer and consumer reader of content present in booktube from the reflections of Santaella (2013), as well as its protagonism as a mediator of readings on YouTube. Briefly and connected to what we observed in booktube, we reviewed the history of reading practices, the different types of readers and the relationships with the technologies available at each time (CAVALLO; CHARTIER, 1997; CHARTIER, 1998). With that in mind, we question the nature of ruptures and continuities presenting the ways of reading of the reader investigated by the research. We discussed the space in which booktubers are inserted and the production of literary content by non-specialized readers on the Internet. In the context of the convergence culture and the rise of the influence of prosumers, we problematized the mediation of reading in environments such as YouTube, a mix of social network, sharing platform and business model (BURGESS; GREEN, 2009; SHIRKY, 2011; JENKINS; GREEN; FORD, 2014). Methodologically, we opted for pragmatic analysis of narrative (MOTTA, 2013), a proposal that focuses on three main axes in narratives: language, content and background themes. Based on these examination plans, we will try to understand how the cognitive, affective, argumentative and symbolic dimensions of reading are presented (JOUVE, 2002) in Pam Gonçalves' video selection. Keywords: Booktube. Narrative. Reading mediation.